Evaluating Hydrogen Production from Grape Pomace Gasification: Unveiling the Potential for Chile S Wine Industry and Its Solid Waste Recovery as Energy Source - Serafini, D; Garrido-Lazo, R; Rodriguez-Machuca, P (Elsevier Ltd, 2024)
This study presents the characteristics of fluidized bed gasification of grape pomace, which is a residual biomass from the Chilean wine industry, by means of sensitivity analysis in the Aspen Plus process simulator. The model was used to evaluate the hydrogen generation potential and identify optimal conditions to improve hydrogen production. The effects of gasification temperature on syngas composition, syngas exergy and gasification efficiency were examined. Sensitivity analysis revealed that gasification temperatures above 800 °C result in the highest hydrogen yield. In addition, a mapping analysis of vineyards in Chile indicates a regional hydrogen production potential of 17,109.26 tons per year by pomace gasification. The results are accompanied by an economic and environmental assessment based on the model results, ensuring a holistic evaluation of the proposed approach. © 2024 Elsevier Ltd